THE IMPACT OF LIFESTYLE FACTORS ON THE INTENSITY OF ADVERSE EFFECTS IN SINGLE AND REPEATED SESSION PROTOCOLS OF TRANSCRANIAL ELECTRICAL STIMULATION: AN EXPLORATORY PILOT STUDY - Aaron Kortteenniemi; Alfredo Ortega-Alonso; Amir-Homayoun Javadi; Owen Thomas; Tommi Tolmunen; Tuukka Kotilainen; Jan Wikgren; Soili M. Lehto (Psychiatria Fennica, 2020)
Transcranial electrical stimulation (tES) has shown promise in the treatment of conditions such as depression and chronic pain with mild-to-moderate adverse effects (AEs). Few previous studies have attempted to identify factors predicting tES-induced AEs. In particular, AEs resulting from repeated sessions of tES remain understudied. We conducted an exploratory retrospective analysis of two independent randomized controlled studies to investigate whether lifestyle factors (i.e. chronic alcohol use, smoking, exercise, and quality and length of sleep) modify the severity and frequency of tES-induced AEs, and evaluated the progression of AEs over repeated sessions. We utilized two double-blinded samples: 1) a male sample (n=82) randomized to receive transcranial direct current stimulation (tDCS) or sham for 5 days, and 2) a mixed-sex sample (n=60) who received both transcranial random noise stimulation (tRNS) and sham in a crossover setting. The severity of AEs was recorded on a scale of 0-100. The data was analysed using negative binomial models. In addition, we performed power calculations and, to guide future research, evaluated the numbers of individuals needed to detect non-significant observations as significant. By day 5, the tDCS group experienced more sensations under the electrodes than the sham group. Alcohol use, smoking, exercise, or quality or duration of sleep did not appear to be associated with the intensity of the AEs. The subsequent power analyses indicated that substantially larger samples would be needed to detect the observed associations as significant. Repetitive sessions do not appear to introduce additional AE burden to individuals receiving either tDCS or tRNS, at least with protocols lasting up to 5 days. Alcohol use, smoking, exercise, or quality or duration of sleep appear to only have an effect of negligible size, if any, on AEs induced by tDCS or tRNS, and studies with sample sizes ranging from roughly 100 individuals to hundreds of thousands of individuals would be required to detect such effects as significant.